2018
DOI: 10.1002/1873-3468.12941
|View full text |Cite
|
Sign up to set email alerts
|

Human viperin catalyzes the modification of GPP and FPP potentially affecting cholesterol synthesis

Abstract: Viperin is a radical SAM enzyme that possesses antiviral properties against a broad range of enveloped viruses. Here, we describe the activity of human viperin with two molecules of the mevalonate pathway, geranyl pyrophosphate, and farnesyl pyrophosphate, involved in cholesterol biosynthesis. We postulate that the radical modification of these two molecules by viperin might lead to defects in cholesterol synthesis, thereby affecting the composition of lipid rafts and subsequent enveloped virus budding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 40 publications
0
13
1
Order By: Relevance
“…Our work presented here reached different conclusions when compared with two recent studies of in vitro reconstitution of the viperin-catalyzed reactions (37,38). First, Honarmand Ebrahimi et al (37) reported an in vitro study of the recombinant viperin from fungal Thielavia terrestris (TteViperin), indicating the radical addition of 5Ј-dA ⅐ to UDPglucose.…”
Section: Catalysis Of Radical C-c Double Bond Addition By Viperincontrasting
confidence: 54%
See 2 more Smart Citations
“…Our work presented here reached different conclusions when compared with two recent studies of in vitro reconstitution of the viperin-catalyzed reactions (37,38). First, Honarmand Ebrahimi et al (37) reported an in vitro study of the recombinant viperin from fungal Thielavia terrestris (TteViperin), indicating the radical addition of 5Ј-dA ⅐ to UDPglucose.…”
Section: Catalysis Of Radical C-c Double Bond Addition By Viperincontrasting
confidence: 54%
“…The recently published crystal structure of viperin from Mus musculus (Mmu-Viperin) provides molecular insight into viperin as a radical SAM enzyme (36), but the study did not reveal possible biological substrate(s) of viperin. More recently, two studies described the in vitro reconstitution of viperin-catalyzed reactions and resulted in two different conclusions (37,38). Based on our study presented here, we have disagreements with both studies, and we will discuss them below.…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…Various studies had previously linked viperin to the downregulation of cholesterol biosynthesis (39, 46, 55), but the effect of viperin expression of cellular cholesterol biosynthesis had not been investigated. To examine this question, HEK293T cells were grown in reduced serum media containing lipoprotein-depleted serum to minimize uptake of exogenous cholesterol (56).…”
Section: Resultsmentioning
confidence: 99%
“…Various studies had previously linked viperin to the downregulation of cholesterol biosynthesis (39, 46,55), but the effect of viperin expression on cellular cholesterol biosynthesis had not been investigated.…”
Section: Viperin Expression Reduces Cholesterol Biosynthesismentioning
confidence: 99%